KONDISI SOSIAL EKONOMI DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA NELAYAN SKALA KECIL DI DESA SAPEKEN, SUMENEP, JAWA TIMUR - Rengga Pandesta; I Ketut Wija Negara; I Wayan Restu (Universitas Pattimura, 2025)
Fishermen are the primary source of livelihood for the community in Sapeken Village, Sumenep, East Java. This study aims to assess the socioeconomic conditions and welfare levels of fishermen, measured through 10 indicators: household income, household expenditure, housing ownership, housing facilities, education of household members, health of household members, access to healthcare facilities, access to transportation facilities, safety from crime, and access to information and communication technology. Data were collected from 93 respondents between June and July 2024 over a period of two weeks. All respondents answered the same questions using a scale from one to three, and the weighted scores were totaled and averaged to produce three categories: prosperous, moderate, and less prosperous. The educational background of fishermen in Sapeken is mostly at the Senior High School level, with an average income exceeding IDR 2,249,000. Based on social conditions, the fishermen fall into a good category. Likewise, the economic conditions of the fishermen's households are also in good standing. The overall socioeconomic conditions of fishing households in Sapeken Village are classified as good, with a total score of 2.75 from the 10 parameters, indicating a high level of welfare. A score between 2.41 and 3.11 suggests that the fishing households are prosperous.